Maternal Residence Near Agricultural Pesticide Applications and Autism Spectrum Disorders among Children in the California Central Valley. - Roberts EM; English PB; Grether JK; Windham GC; Somberg L; Wolff C (Environmental Health Perspectives, 2007)
BACKGROUND: Ambient levels of pesticides ('pesticide drift') are detectable at residences near agricultural field sites. OBJECTIVE: Our goal was to evaluate the hypothesis that maternal residence near agricultural pesticide applications during key periods of gestation could be associated with the development of autism spectrum disorders (ASD) in children. METHODS: We identified 465 children with ASD born during 1996-1998 using the California Department of Developmental Services electronic files, and matched them by maternal date of last menstrual period to 6,975 live-born, normal-birth-weight, term infants as controls. We determined proximity to pesticide applications using California Department of Pesticide Regulation records refined using Department of Water Resources land use polygons. A staged analytic design applying a priori criteria to the results of conditional logistic regressions was employed to exclude associations likely due to multiple testing error. RESULTS: Of 249 unique hypotheses, four that described organochlorine pesticide applications--specifically those of dicofol and endosulfan--occurring during the period immediately before and concurrent with central nervous system embryogenesis (clinical weeks 1 through 8) met a priori criteria and were unlikely to be a result of multiple testing. Multivariate a posteriori models comparing children of mothers living within 500 m of field sites with the highest nonzero quartile of organochlorine poundage to those with mothers not living near field sites suggested an odds ratio for ASD of 6.1 (95% confidence interval, 2.4-15.3). ASD risk increased with the poundage of organochlorine applied and decreased with distance from field sites. CONCLUSIONS: The association between residential proximity to organochlorine pesticide applications during gestation and ASD among children should be further studied.